Effects of Childhood Peers on Personality Skills - Shuaizhang Feng; Jun Hyung Kim; Zhe Yang (Institute of Labor Economics (IZA), 2021)
Despite extensive literature on peer effects, the role of peers on personality skill development remains poorly understood. We fill this gap by investigating the effects of having disadvantaged primary school peers, generated by random classroom assignment and parental migration for employment. We find that having disadvantaged peers significantly lowers conscientiousness, agreeableness, emotional stability, and social skill. The implied effects of a 10–15 percentage point change in the classroom proportion of disadvantaged peers are comparable to the effects of popular early childhood interventions. Furthermore, we find suggestive evidence that these effects are driven by the peers' personality skills.
Keywords: I21; D62; O15; 330; peer effect; noncognitive skill; left-behind children; human capital; Big-5